1999
DOI: 10.1029/1999jd900105
|View full text |Cite
|
Sign up to set email alerts
|

Measuring gravity wave momentum fluxes with airglow imagers

Abstract: Abstract. We describe a new technique for estimating the vertical fluxes of horizontal momentum in the mesopause region using airglow imager data. The azimuthal distribution of the relative airglow intensity or rotational temperature variance associated with both monochromatic and quasi-random waves is computed from the unambiguous twodimensional horizontal wave number spectrum. The variance distribution is used in a gravity wave model to predict the cross-correlation coefficient between the vertical and horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 21 publications
0
54
0
Order By: Relevance
“…In addition, successfully validated the momentum fluxes derived using this imager-spectra technique against those measured directly by a dual-beam Na wind lidar. Due to the extended gravity-wave spectrum observed, Swenson et al (1999) found that the magnitudes of the imager-spectra and Na-lidar momentum fluxes reported by Gardner et al (1999) were larger than those derived from imaging specific monochromatic waves or the climatological values derived from radars (Vincent, 1984). Thus, only momentum-flux magnitudes derived using this same imagerspectra technique described by will be compared here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, successfully validated the momentum fluxes derived using this imager-spectra technique against those measured directly by a dual-beam Na wind lidar. Due to the extended gravity-wave spectrum observed, Swenson et al (1999) found that the magnitudes of the imager-spectra and Na-lidar momentum fluxes reported by Gardner et al (1999) were larger than those derived from imaging specific monochromatic waves or the climatological values derived from radars (Vincent, 1984). Thus, only momentum-flux magnitudes derived using this same imagerspectra technique described by will be compared here.…”
Section: Discussionmentioning
confidence: 99%
“…The technique for estimating momentum fluxes using airglow imager data in this way has been described fully by Gardner et al (1999), and can be used to estimate the momentum fluxes associated with the full spectrum of both monochromatic as well as quasi-random wave perturbations. The technique has been validated against Na wind lidar measurements of momentum flux when applied to both monochromatic waves and the full wave spectrum , and has been used to infer the seasonal variation of the momentum flux in the Northern and Southern Hemispheres Espy et al, 2004) Briefly, the 3-D Fourier spectrum in frequency, ω, and the zonal, k, and meridional, l, horizontal wave numbers, was computed for the nightly sequence of all-sky Na images using the processing techniques detailed in Gardner et al (1996) and Coble et al (1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, there is considerable interest in measuring momentum fluxes carried by those waves (Holton, 1982;Gardner et al, 1999). Co-located optical imagers and radar wind instruments (mean horizontal wind information) at the same observation site are combined to provide intrinsic wave parameters (frequency, horizontal wavelength, direction of propagation), determined directly from the airglow Correspondence to: F. Vargas (fabio.vargas.br@gmail.com) images.…”
Section: Introductionmentioning
confidence: 99%